Silencing of Oleuropein β-Glucosidase Abolishes the Biosynthetic Capacity of Secoiridoids in Olives - Koudounas, Konstantinos; Thomopoulou, Margarita; Rigakou, Aimilia; Angeli, Elisavet; Melliou, Eleni; Magiatis, Prokopios; Hatzopoulos, Polydefkis (Frontiers in Plant Science, 2021)
Specialized metabolism is an evolutionary answer that fortifies plants against a wide spectrum of (a)biotic challenges. A plethora of diversified compounds can be found in the plant kingdom and often constitute the basis of human pharmacopoeia. Olive trees (Olea europaea) produce an unusual type of secoiridoids known as oleosides with promising pharmaceutical activities. Here, we transiently silenced oleuropein β-glucosidase (OeGLU), an enzyme engaged in the biosynthetic pathway of secoiridoids in olive tree. Reduction of OeGLU transcripts resulted in the absence of both upstream and downstream secoiridoids in planta, revealing a regulatory loop mechanism that bypasses the flux of precursor compounds towards the branch of secoiridoid biosynthesis. Our findings highlight that OeGLU could serve as a molecular target to regulate the bioactive secoiridoids in olive oils.